Caracterização microestrutural de liga de alumínio AA8011 reciclado de embalagem pós-consumo da indústria de alimentos - AFONSO, Larissa Corrêa (2019)
Aluminum among its many properties can be infinitely recycled. In this work, the ingots obtained from the recycling of aluminum from post-consumer packaging used in the food industry, produced with the AA 8011 alloy, were obtained and characterized. The boiling pans were collected, sanitized, comminuted and cast. The ingots obtained were characterized using chemical analysis, X-ray fluorescence, X-ray Dispersive Energy (EDS). The macro and microstructure and the mechanical property were investigated in detail using optical microscopy, optical microscopy and scanning electron microscopy, and Vickers microhardness assay. The results of EDS characterization and X-ray fluorescence allow evaluating the alloy as AA8011. The macrostructure revealed low porosity index and small inclusions. The microstructure had a dendritic structure and is more refined at the metal-mold interface than at the center of the ingot. The Vickers microhardness showed a result of 35.54 HV.